The Acceptance of Technology Influential to the Intention of Payment Via Smart Phones Among Generation X in Bangkok - ธนสารโสภณ ธัญรดา; ทวีสุข พีรภาว์ (Community and Social Development Journal, 2019)
The objective of this study was to explore the acceptance of technology influential to the intention of payment via smart phones among generation X in Bangkok by employing the quantitative research methodology. Sample group which study are generation x of 400 people who living in Bangkok between the ages of 39-53 year olds. The information from the dwellers was garnered through questionnaires. Descriptive statistics, which includes frequency, percentage, mean and standard deviation, was used to analyze the information. The assumption of this study was assessed by multiple regression analysis. The result of assumption assessment indicated that the acceptance of technology influential to the intention of payment via smart phones among generation X inBangkok could be classified into aspects-attitude of utilization, social influence and risk perception. They accounted for the acceptance of technology influential to the intention of payment via smart phones among generation X in Bangkok around 62%. When taking the regression coefficient into consideration, it revealed that the acceptance on the aspect of attitude of utilization (β =0.479) has the most influence towards the intention of payment via smart phones among generation X in Bangkok. Whereas the acceptance on the aspect of social influence came second (β =0.091) in terms of intention of payment via smart phones among generation X in Bangkokand the acceptance on the aspect of Risk perception came third (β =0.237) in terms of intention of payment via smart phones among generation X in Bangkok.